A case report of an improvement in premature ventricular complex–induced cardiomyopathy following continuous positive airway pressure therapy in a patient with severe obstructive sleep apnoea. Issue 9 (22nd August 2022) - Sakai, Togo; Takemoto, Masao; Koga, Tokushi; Tsuchihashi, Takuya
Abstract: Background: Premature ventricular complexes (PVCs) are the most common arrhythmias observed in patients without structural heart disease (SHD). Frequent PVCs cause left ventricular dilation and dysfunction without SHD, the so-called PVC-induced cardiomyopathy (PIC). Obstructive sleep apnoea (OSA) is a highly prevalent disease worldwide and is strongly associated with arrhythmias including PVCs. PVCs have been reported in up to two-thirds of patients with OSA. Continuous positive airway pressure (CPAP) is a well-established primary treatment modality in patients with moderate-to-severe OSA. Case summary: We present a 69-year-old male case with severe OSA and an improvement in his PIC following CPAP therapy. He has remained well without any symptoms or arrhythmias for 2 years after the introduction of the CPAP therapy for his OSA. Discussion: Using CPAP therapy for the treatment of his OSA, we could improve his PIC in accordance with a reduction in frequent PVCs without ablation of the PVCs. Only ablation without CPAP therapy may not be able to completely treat PIC associated with OSA, as in the present case. Thus, physicians should be aware of the possibility of PVCs associated with OSA when examining patients with PVCs. To the best of our knowledge, this is the first report of a case of improvement in PIC following CPAP therapy in a patient with severe OSA. Future investigations should focus on whether CPAP therapy can improve PIC associated with OSA and prevent a progression to heart failure and also result in an improvement in the prognosis.